ANALISIS FERTILITAS DAN MIGRASI TERHADAP PERTUMBUHAN PENDUDUK - Ayu Ramadani; Asnidar (Fakultas Ekonomi Universitas Samudra, 2022)
This study aims to determine and analyze the effect of partial fertility on population growth and analyze the effect of partial migration on population growth, as well as analyze the effect of fertility and simultaneous migration on population growth. The data used are secondary data in the form of time series data and obtained from the Central Agency Statistics (BPS) of Aceh Tamiang District, Sub-district Office and Seruway Public Health Center 2012-2020. The data analysis method used Multiple Linear Regression analysis with the Classic Ordinary Least Squares (OLS) method using Eviews 10 software. The results showed that partially fertility had a positive and significant effect on population growth in Seruway District, while migration partially positive and significantly affected population growth in Seruway District. Seruway District. Simultaneously fertility and migration have a significant effect on population growth in Seruway District.